Hadis Yorumunda Zamanın Ruhunu Anlamak ve İnterdisipliner Perspektif - Demirel, Serdar (FSM Vakıf Üniversitesi, 2014)
İslâm âlimleri Hz. Peygamber’den bize ulaşan hadislerin ṣaḥiḥ olup olmadıklarını, onların muhtevasını doğru anlamak ve zamanın değişen şartlarına göre yorumlayabilmek için büyük çaba göstermişlerdir. Hadis ilimleri bu gayretlerin tabiî sonucu olarak doğmuş ve zaman içerisinde gelişmiştir. Bu da hadisleri doğru anlamak için konulmuş disiplin ve kaidelerin geliştirilmeye açık dinamik yapısını işaretler. Biz de bu çalışmada hadislerin amacına daha uygun yorumlanabilmesi için çağdaş hadis yorumcusunun daha önceden yapılmış metin anlama tekniklerine ilaveten yeni donanımlara muhtaç olduğunu göstermeye çalıştık. Bu meyanda hadis yorumcusunun içinde yaşadığı çağın ruhuna, bu çağı yöneten dünya görüşüne vakıf olmasının gerekliliğini ve interdisipliner perspektifin sunabileceği müsbet katkıları inceledik.

Throughout history, Muslim scholars have strived to understand the true meaning of the Prophet’s (pbuh) aḥadīth and interpret them according to the changing conditions of the time. Sciences of Ḥadīth emerged specifically to meet two objectives; first, to distinguish authentic aḥadīth from fabricated ones via the chains of report and texts criticism and second, to elaborate it further in order to meet any new conditions or changes introduced into life with the passage of time. Sciences of Ḥadīth and its sub-disciplines are open to further development. The evolving structure of the Sciences of Ḥadīth from its succinct form to its current elaborate structure is clear evident of its dynamic and progressive character. In this study, the researcher focuses on additional critical points in the pursuit of gaining a better understanding of aḥadīth, such as comprehending the spirit of the time and adopting an interdisciplinary perceptive.
Understanding the Spirit of Time and Interdisciplinary Perspective in the Interpretation of Ḥadith
Keywords: Yorumlama; Hadis Metinleri; Zaman Ruhu; İnterdisipliner Perspektif; Interpretation; Ḥadith texts; Spirit of Time; Interdisciplinary Perspective